Post-COVID sequelae effect in chronic fatigue syndrome: SARS-CoV-2 triggers latent adenovirus in the oral mucosa - Hannestad, Ulf; Apostolou, Eirini; Sjögren, Per; Bragée, Björn; Polo, Olli; Bertilson, Bo Christer; Rosén, Anders (Frontiers in Medicine, 2023)
The post-viral fatigue syndromes long COVID and myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) have multiple, potentially overlapping, pathological processes. These include persisting reservoirs of virus, e.g., SARS-CoV-2 in long COVID patient’s tissues, immune dysregulation with or without reactivation of underlying pathogens, such as Epstein–Barr virus (EBV) and human herpesvirus 6 (HHV6), as we recently described in ME/CFS, and possibly yet unidentified viruses. In the present study we tested saliva samples from two cohorts for IgG against human adenovirus (HAdV): patients with ME/CFS (n = 84) and healthy controls (n = 94), with either mild/asymptomatic SARS-CoV-2 infection or no infection. A significantly elevated anti-HAdV IgG response after SARS-CoV-2 infection was detected exclusively in the patient cohort. Longitudinal/time analysis, before and after COVID-19, in the very same individuals confirmed HAdV IgG elevation after. In plasma there was no HAdV IgG elevation. We conclude that COVID-19 triggered reactivation of dormant HAdV in the oral mucosa of chronic fatigue patients indicating an exhausted dysfunctional antiviral immune response in ME/CFS, allowing reactivation of adenovirus upon stress encounter such as COVID-19. These novel findings should be considered in clinical practice for identification of patients that may benefit from therapy that targets HAdV as well.